The effect of online reading on argumentative essay writing quality. - Antoon De Rycker; Prema Ponnudurai (Penerbit UKM, 2011)
In tertiary education in Malaysia, essay-writing assignments are central to most English as a Second Language (ESL) courses. Often reading texts are used as a stimulus to better writing but it has not yet been extensively researched whether these texts should be presented on screen or on paper. This study examines which of these two presentation modes, viz., interactive online reading or print-based reading, help today’s ICT-literate generation of Malaysian students write better argumentative essays. The rationale is that interactive online reading motivates these students more, and that this higher task motivation in its turn leads to more successful task performance. Using a quasiexperimental,between-subjects research design, we elicited a total of 90 essays (31,207 words), 44 of which written by students reading the input text online and 46 by students reading the same text on paper. The quality of argumentation was analysed, using a modified three-way version of Harrell’s (2005) coding rubric: thesis, support and counter-arguments. Our comparative study shows that 61% of all essays are ‘good’, with 39% rated as ‘average’ to ‘poor’. Results indicate that the interactive online reading condition yields superior task performance and that it also produces proportionately more essays with a ‘good’ thesis statement. Both findings are statistically significant. Essays with a ‘good’ thesis are more likely to contain ‘good’ support though not always ‘good’ counter-arguments. Counter-argumentation remains underdeveloped for both conditions.As a springboard to better argumentative content, ICT-enabled reading-based activities may not suffice, leaving room for other pedagogic interventions.